2023
DOI: 10.1177/17562848231188586
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in patients with liver disease and liver transplant: clinical implications, prevention, and management

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has had enormous implications for the care of patients with chronic liver disease (CLD), cirrhosis, and liver transplant (LT). Clinical outcomes of COVID-19 vary in patients with CLD and cirrhosis compared to healthy controls, and in patients with LT compared to patients without LT. Several special considerations apply to the approach to vaccination and treatment in patients with CLD and LT. The practice of liver transplantation has also been heavily impacted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…As compared to individuals without CLD, the patients with CLD and cirrhosis may have more severe disease and a greater COVID-19-associated mortality rate. According to a system review, likelihood of COVD 19 associated severe diseases and death was 2.44 times greater in patients with CLD compared to those without underlying liver diseases 45,46 .…”
Section: Impact Of Covid-19 On Patients With Pre-existing Liver Disor...mentioning
confidence: 99%
“…As compared to individuals without CLD, the patients with CLD and cirrhosis may have more severe disease and a greater COVID-19-associated mortality rate. According to a system review, likelihood of COVD 19 associated severe diseases and death was 2.44 times greater in patients with CLD compared to those without underlying liver diseases 45,46 .…”
Section: Impact Of Covid-19 On Patients With Pre-existing Liver Disor...mentioning
confidence: 99%
“…Nonetheless, the situation becomes more complicated among individuals with pre-existing hepatic disorders-mainly non-alcoholic fatty liver disease (NAFLD), MAFLD and cirrhosis [179][180][181]. On the other hand, previously diagnosed viral hepatitis was not found as a triggering factor for liver damage after being infected with the coronavirus [182]. According to global data, the overall risk of a severe course and death because of COVID-19 in patients with CLD becomes 2.44 times greater in comparison to the population with no hepatic problems [183][184][185].…”
Section: Covid-19 In Patients With Pre-existing Liver Failure-general...mentioning
confidence: 99%
“…Another source of data revealed that in 2020 ALD constituted 40.1% of all LT listings and this result was greater than cases related to hepatitis C virus (HCV) and NASH taken together. Another retrospective study performed in the United States between March 2020 and September 2022 showed a more pronounced mortality due to ALD, cirrhosis and hepatic failure in all; the excess risks were 1.4-2.8 times higher [182,203]. One could ask: why?…”
Section: Ethanol Liver and Covid-19-a Global Perspectivementioning
confidence: 99%